Rural Surgery: Time for a new specialty! - Joshi, Arbin (Journal of General Practice and Emergency Medicine of Nepal, 2010)
One of the demands of the Alma declaration of the WHO to which Nepal is a signatory was that health should be available to all and a proper referral system must be developed as a part of total health care. This is lacking in most developing countries, including Nepal. A large number of medical colleges and private hospitals have sprung up in large cities, all without any proper referral system to cover the rural population. As a result even today women die of obstructed labour in the countryside while transplants and bypass operations are being done in the large cities.